Other-Regarding Preferences and Redistributive Politics - Ernst Fehr; Thomas Epper; Julien Senn (Center for Economic Studies and ifo Institute (CESifo), 2022)
Increasing inequality and associated egalitarian sentiments have again put redistribution on the political agenda. Other-regarding preferences may also affect support for redistribution, but knowledge about their distribution in the broader population and how they are associated with political support for redistributive policies is still scarce. In this paper, we take advantage of Swiss direct democracy, where people voted several times on strongly redistributive policies in national plebiscites, to study the link between other-regarding preferences and support for redistribution in a broad sample of the Swiss population. We document that inequality aversion and altruistic concerns play a quantitatively large positive role in the support for redistribution, in particular for more affluent individuals. In addition, previously identified key motives underlying opposition to redistribution – such as the belief that effort is an important driver of individual success – play no role for selfish individuals but are highly relevant for altruistic and egalitarian individuals. Finally, while inequality averse individuals display strong support for policies that primarily aim at reducing the incomes of the rich, altruistic individuals are considerably less supportive of such policies. Thus, knowledge about the fundamental properties and the distribution of individuals' other-regarding preferences also provides a deeper understanding about who is likely to support specific redistributive policies.
Keywords: D31; D72; H23; H24; 330; social preferences; altruism; inequality aversion; preference heterogeneity; demand for redistribution